Mechanisms of psychological resiliency in women after mastectomy - Kaczmarek, Łukasz D.; Sęk, Helena; Ziarko, Michał; Marzec, Marta (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : To investigate into the mechanisms of resiliency in women after mastectomy. We hypothesized that the mechanism of resiliency in women with breast cancer would involve facilitation of adaptive coping strategies and inhibition of maladaptive strategies. We tested a mediational model in which resiliency was related to satisfaction with life through coping strategies. Material and methods : Thirty women after mastectomy aged 28–69 years (M = 53.23, SD = 9.00) completed the Ego Resiliency Scale, Mental Adjustment to Cancer Scale, and Satisfaction with Life Scale. Results : The bootstrapping technique revealed that there were significant indirect effects for positive reframing (95% CI: 0.01–0.36), hopelessness/helplessness (95% CI: 0.18–0.83) and anxious preoccupation (95% CI: 0.001–0.55) but not for fighting spirit. The models explained up to 33% of the variance in satisfaction with life. Conclusions: Coping strategies fully explain the effect of resiliency on satisfaction with life in women after mastectomy. This finding provides additional evidence of the fundamental role of coping strategies in the mechanisms of resiliency. We obtained similar results in patients with type II diabetes and rheumatoid arthritis. The lack of significant associations of fighting spirit with resiliency suggests that this coping strategy may be beneficial for somatic health but its contribution to the mechanisms of psychological resiliency is complex.